Web, semantic web and pragmatic web: Position of Information Architecture - Vidotti, Silvana Aparecida Borsetti Gregorio; Coneglian, Caio Saraiva [UNESP]; Roa-Martínez, Sandra Milena [UNESP]; Vechiato, Fernando Luiz [UNESP]; Segundo, José Eduardo Santarém [UNESP] (Universidade Federal da Paraíba, 2019)
The expansion in the use of digital information environments, especially the Web, has brought to the need of improving the interaction between individuals and computational mechanisms. In this regard, the Web makes it possible to publish content, the Semantic Web seek to insert meaning to the contents available in the Web, while the Web Pragmatic look to add the context of these contents. Information Architecture seeks to provide theoretical and applied subsidies for the digital environments creation that can meet the user’s information needs, considering also the context and content. In this way, it is questioned how the theories and fields related to Information Architecture, studied by Information Science, are related to the Web, Semantic Web and Pragmatic Web. Thus, this paper aims to identify and explore the relationship between Information Architecture, Web, Semantic Web and Pragmatic Web. For this, a qualitative methodology was used, with a bibliographic and analytical character. As results, it was identified that the Information Architecture, having as its prism its systemic theory, is improved when it makes use of Semantic Web, while Information Architecture with of the fields of studies that use of its theoretical framework, such as Information Findability, Usability, Pervasiveness and User Experience, promoting the materialization of the Pragmatic Web. It was concluded that the existing relationship occurs when the Information Architecture enriched with its fields of study incorporates the technologies of the Semantic Web and, it becomes a facilitator of the Web Pragmatic.
Web, web semântica e web pragmática: Um posicionamento da Arquitetura da Informação
Keywords: Information Architecture; Pragmatic contexts; Pragmatic Web; Semantic Web; Web